Diversidade genética da espécie dioica Myrsine coriacea (Primulaceae) da Floresta Atlântica - Paschoa, Roberta Pena da (2017)
Myrsine coriacea is a species of the family Primulaceae represented by dioic trees or shrubs, found in all the phytophysiognomies of the Atlantic Forest. The individuals of M. coriacea in natural environments present an aggregated spatial distribution pattern, forming isolated populations, usually established in open areas or in the process of regeneration. The influence of this isolation on genetic diversity in natural populations of the species is unknown. Nevertheless, M. coriacea is used in reforestation programs in Brasil, since it has a high production capacity of attractive fruits to the avifauna, potentiating the seed rainfall process. In addition, canopy shading helps to suppress grasses, facilitating the establishment of seedlings of other species of Angiosperms. Obtaining seeds for this purpose, however, has been performed without considering the genetics of the matrices. Genetic diversity corresponds to the number of alleles per locus and how these are alleles are distributed in the population. Their measurement in and out as populations can provide important information for conservation and management of natural resources. The objective of this study was to measure an intrapopulational, interpopulational genetic diversity and between male and female individuals in natural populations of M. coriacea in Atlantic Forest areas. Therefore, we estimated: 1. a magnitude and a distribution of genetic variation within populations; 2. genetic dissimilarity between each pair of individuals within populations; 3. The generic flow and degree of differentiation between populations; And 4.spatial structuring of genetic variability. The results indicate high levels of polymorphism and genetic diversity in M. coriacea. The greater genetic diversity within populations compared to moderate gentic differentiation among them, indicates that there is an interpopulation gene flow, despite the distance and isolation to which the populations are subjected and. Multivariate analyzes detected significant differences between populations, but not between individuals of different sexes, with no significant interaction between the sex and locality factors. As analyzes of genetic diversity carried out for males and females also do not indicate genetic differences between the sexual morphs. The results suggest that the studied populations conserve intrapopulational genetic diversity despite the isolation and, due to the high intrapopulational genetic diversity, with potential for marking of matrices for the purpose of collecting seeds for reforestation purposes